Kompetensi Guru Taman Pendidikan Al-Quran (TPA) Terhadap Kemampuan Santri - Yunita, Yuyun (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2016)
Competencies are the knowledge, skills and values ​​reflected in the basic habits of thinking and acting. Teachers are responsible adults who provide guidance and assistance to students in the physical and spiritual development in order to reach maturity, and able to carry out his duties as a creature of God, the caliph surface of the earth, as social beings, and as individuals who are able to stand alone. Parks Quran Education serves as a non-formal institutions in order to avoid the decline of religion and the Qur'anic generation, ability to read the Qur'an is an indicator of the quality of religious life of a Muslim, therefore read the Qur'an movement is a step in the strategy in order to improve the quality of people especially Muslims and success of development in the field of religion.